2014
DOI: 10.1371/journal.pone.0100989
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Transcriptional Patterns and Mycological Phenotypes following Infection of Fusarium graminearum by Four Mycoviruses

Abstract: Many fungi-infecting viruses, which are termed mycoviruses, have been identified, and most do not cause any visible symptoms. Some mycoviruses, however, can attenuate the virulence of the infected fungi, a phenomenon referred to as hypovirulence. To study fungus responses to virus infection, we established a model system composed of Fusarium graminearum and four mycoviruses including FgV1 (Fusarium graminearum virus 1), FgV2, FgV3, and FgV4. FgV1 and FgV2 infections caused several phenotypic alterations in F. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
109
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(115 citation statements)
references
References 30 publications
6
109
0
Order By: Relevance
“…As previously reported, the expression of genes involved in dsRNA-mediated gene silencing is strongly induced in response to viral infection Lee et al, 2014). Thirteen F. graminearum genes responsible for PTGS were selected to examine the effect of FgHV2/JS16 on the expression of these genes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As previously reported, the expression of genes involved in dsRNA-mediated gene silencing is strongly induced in response to viral infection Lee et al, 2014). Thirteen F. graminearum genes responsible for PTGS were selected to examine the effect of FgHV2/JS16 on the expression of these genes.…”
Section: Discussionmentioning
confidence: 99%
“…Total RNAs were extracted with a Fungal RNA kit (OMEGA) according to the manufacturer's instructions, treated with DNase I (TaKaRa Bio Inc.) to completely remove genomic DNA, and suspended in DEPC-treated water. The synthesis of cDNAs was performed with M-MLV reverse transcriptase (Promega) and an oligo d (T) primer to quantify mRNA expression (Lee et al, 2014). Relative quantitative real-time RT-PCR (qRT-PCR) was performed on a CFX96 Real-Time PCR System (Bio-Rad, Herculess, U. S.A.) using the TransStart s Green qPCR SuperMix UDG (TransGen) according to the manufacturer's instructions.…”
Section: Impact Of the Virus On The Host Biological Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Although CHV1-Euro7 shares a high level of sequence identity at both the nucleotide (87% to 93%) and the amino acid (90% to 98%) levels with CHV1-EP713, significant differences in the C. parasitica transcriptome were observed. Based on the application of next-generation sequencing technology, Lee et al recently reported transcriptional changes following the infection of F. graminearum with four mycoviruses from four different families [16]. There has been extensive research on the gene expression changes that occur in C. parasitica infected with hypoviruses such as CHV1/EP713 and CHV1-Euro7 compared with the wild-type strain.…”
Section: Introductionmentioning
confidence: 99%